Resource-Based Conflicts in Africa: The Socio-political and Economic Analysis of the Oil-bearing Region in the Nigerian Federation - Nwosu, Ikechukwu Jude Donald (EBSU Journal of Social Sciences and Humanities, 2021)
There is no doubt that Africa is a continent riddled with conflicts. Apart from conflicts arising from the contest for political power, one major source of conl1ict in the continent is the struggle for resource control. In Nigeria, the contest for resource control has, very often, been bitterly fought on account of the peculiar circumstances in the country. Nigeria is a country blessed with stupendous natural endowments particularly crude oil. This crude oil is got from the Oil-Bearing Region known as the Niger-Delta area of the country. Despite the enormous amount or money derived from the exploitation of oil in the region, the Niger-Delta is still very under-developed. The people of the region have risen in arms against the Nigerian state demanding for the control of the resources derived from their area. The Nigerian state has responded to contain the rising crisis in the region but the situation has degenerated into serious conflict. This paper takes a look at this Resource Based Conflict in the Niger-Delta region with the aim of discussing the socio-political and economic analysis of the oil-bearing region and at the same time take a look in the conflict which is herein identified as environment degradation and concludes that the Nigerian state must adopt participatory strategies in the management of this resource and the thorough-going empowerment and development of the region